2020
DOI: 10.1530/eje-20-0283
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE Immunotherapy of advanced thyroid cancer: from bench to bedside

Abstract: Immunotherapy has arisen in use in the field of oncology with seven immune checkpoint inhibitors approved for the treatment of a variety of cancer histologies. Depending on the cancer type, the success rate might be different, but in average it is about 20%, with some cases showing a durable response, lasting also after the interruption of the treatment, with a clear benefit on OS. The development of an efficacious cure for advanced thyroid carcinomas is still an unmet need and immunotherapy represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
0
23
0
5
Order By: Relevance
“…Additional studies in a mouse model of orthotopic ATC confirmed that increased efficacy in reducing tumor size and improving survival using an anti-PD1/PD-L1 checkpoint inhibitor combined with an MKI (lenvatinib) was associated with a modification of ATC microenvironment (24). Indoleamine 2,3-dioxygenase (IDO1) has been associated with an altered tumor immune response; therefore IDO1 inhibitors are being investigated in clinical trials in combination with other ICIs (25).…”
Section: Introductionmentioning
confidence: 97%
“…Additional studies in a mouse model of orthotopic ATC confirmed that increased efficacy in reducing tumor size and improving survival using an anti-PD1/PD-L1 checkpoint inhibitor combined with an MKI (lenvatinib) was associated with a modification of ATC microenvironment (24). Indoleamine 2,3-dioxygenase (IDO1) has been associated with an altered tumor immune response; therefore IDO1 inhibitors are being investigated in clinical trials in combination with other ICIs (25).…”
Section: Introductionmentioning
confidence: 97%
“…It is urgent to find more effective treatment methods, and immunotherapy has become the focus of attention. Researchers have applied the targeting of immunotherapy to PTC patients who are not sensitive to conventional treatment [33][34][35]. More importantly, studies have shown that the expression of PD-L1 in PTC patients was closely related to lymph node metastasis, suggesting that immunotherapy to inhibit PD-L1 may be a choice for patients with lymph node metastasis [36].…”
Section: Discussionmentioning
confidence: 99%
“…They are used against tyrosine kinase receptors or their ligands, mainly VEGF, to block angiogenesis [82], or more recently targeting immune checkpoint molecules especially in anaplastic thyroid cancer models [83]. Although immunotherapy represents an interesting alternative option also for aggressive thyroid cancer, very few clinical trials have been accomplished and very few studies exploring a way to overcome resistance have been performed [84]. Moreover, none of these agents is associated to molecular biomarkers indicative of response, if not in exploratory studies.…”
Section: Current and Potential Impact Of Molecular Biomarkersmentioning
confidence: 99%